Exploring the Educational Memes in Recent Indo-Pak War - Zunaira Arshad; Muhammad Shoaib Mehmood; Azhar Ahmad (Dialogue Social Science Review (DSSR), 2025)
The present research article entitled “Exploring the Educational Memes in Recent Indo-Pak War”; as its name indicates that it is totally a new work in the realm of educational field; because, there is no single research in which educational memes are explored earlier. In the present research study the researchers collected data from social media resources platform (YouTube, face book, instragram and tik-tok etc.). The congregated data was later analyzed through the content analyses approach and presented in tables and figures. The current research study finds twenty-eight educational memes used by the students and teachers on the different platforms of social media. The masterpiece work is a valuable research because it will pave way for the researchers and it will instigate scholars to conduct more studies to discover new possessions in the education field. Keywords: Educational Memes, Indo-Pak War, Social Media Platform.